Разработка системы учета действий клиентов для WEB-сервиса «дистанционное образование» - Петрушенко, Ю. А. (ХНУРЕ, 2011)
The present thesis is devoted to the tracking system of the client actions for the web-service "Distance education". This system was developed for the correct control of online courses. It allows to automate such process as everyday direct mailing and to generate some necessary documents. Also with this system we can get such information as the transfer of some clients from one course to another one, the payment history, and other client activities. Script language PHP and DBMS MySQL were used to create this tracking system of the client actions.
Keywords: учет действий клиентов; web-приложения